Design for IoT: An Experimental Study to Understand How Design Thinking Can Help in the Elicitation of Requirements for IoT Systems - Souza, Sabrina Rocha de; Meireles, Maria Alcimar; Duarte, José Carlos; Maldonado, Jose Carlos; Conte, Tayana (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Context: The Internet of Things (IoT) consists of networks of physical objects embedded with sensors, software, and other technologies to maintain communication and exchange data over a network. These characteristics bring new challenges to the entire development cycle, including requirements engineering (RE). RE practices have been adapted to meet market dynamics and ensure software quality, using a variety of approaches to support this process. One approach for RE is the use of design thinking (DT) techniques, as IoT systems are closely related to product and service innovation. Objective: To analyze the use of DT techniques in the context of IoT systems, evaluating the support for requirements elicitation. Method: An experimental study was carried out in the context of a practical requirements elicitation activity, aiming to obtain results on the support of DT techniques and their ease of use during requirements elicitation for IoT systems. Results: The statistical test did not show significant differences between the groups that used different sets of techniques. In both groups, participants were able to identify requirements related to the IoT paradigm, such as hardware integration, connectivity, mobility, sensing and actuation. The feedback analysis on the ease of use of the techniques pointed out similar difficulties reported by the participants of the two groups, mainly in relation to the terms present in the templates of the techniques. Conclusion: This article aims to contribute to RE in the IoT context, presenting quantitative data and on the ease of use of DT techniques during the requirements elicitation activity.